Reformasi Administrasi Perpajakan, Implementasi Penerapan E-Faktur dan Kepatuhan Pelaporan Wajib Pajak - Desy Ari Paramitha, Putu; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 31 No 3 (2021)DO - 10.24843/EJA.2021.v31.i03.p02, 2021)
This study aims to determine how the influence of tax administration reforms that are applied as well as the application of e-invoices on tax compliance reporting of taxable entrepreneurs (PKP). The method for determining the sample is using the Accidental Sampling method. The number of samples is 73 respondents obtained from sample calculations with Slovin formula. Data collected by questionnaire. The questionnaire uses a 4-point Likert scale. Data analysis uses multiple linear regression analysis techniques. From the results of data analysis, the results obtained are a positive and significant relationship from the implementation of tax administration reforms and the application of e-invoices to PKP compliance in tax reporting. Keywords:  Tax Administration Reform; E-Invoice Implementation; PKP Reporting Compliance.